A modest method of synthesis Cu- based metal-organic frameworks using benzene dicarbocxylate as a ligan for promising candidate of flue gas CO2 adsorption - MUTTAQIN MUTTAQIN; FARID IMAM HIDAYAT (Jurnal Natural, 2021)
Metal organic framework (MOF) is one of extraordinary materials in many technical field applications. One of them is as CO2 gas adsorbent. We studied, synthesized, and characterized Copper-based material, known as Metal organic frameworks (MOFs), using a solvothermal-based modification method. Copper salt (Cu (NO3)2. 3H2O) and benzene dicarboxylic acid (H2BDC) were mixed and then heated in an oven at 120°C, to produce low impurities, small pore and uniform particle size of materials called CuBDC. Infrared spectroscopy and XRD data confirmed the formation of CuBDC. Furthermore, the result showed that CuBDC frameworks have good thermal stability up to 330°C.  Thereafter SEM picture showed random, layered, and asymmetrical corners structure which is typical of triclinic crystal system. Lastly, specific surface areas and the porosity were analyzed using The Brunauer-Emmett-Teller (BET) method. It recorded 485 m2.g-1 of surface area while average pore volume and average pore size are 0.16 cm3.g-1 and 5.9 Å respectively.   @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536869121 1107305727 33554432 0 415 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ansi-language:IN; mso-fareast-language:IN;}div.WordSection1 {page:WordSection1;}